2014
DOI: 10.4238/2014.october.27.1
|View full text |Cite
|
Sign up to set email alerts
|

BMP-2 promotes chondrogenesis of rat adipose-derived stem cells by using a lentiviral system

Abstract: ABSTRACT. Osteoporosis poses a major public health threat in aging societies. Adipose-derived stem cells (ADSCs) are multipotent adult stem cells that have the ability to yield mesenchymal stem cells, and have the potential to undergo osteogenesis and bone regeneration. Bone morphogenetic proteins (BMPs) have been demonstrated to upregulate bone gene expression after mechanical injury and to improve bone injury repair. This study aimed to produce BMP-2 expression in ADSCs by using lentiviral vectors. Subcutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Nevertheless, during MenSC differentiation, they detected a significant increase in the expression level of Collagen 9A1 and the transcription factor SOX9, suggesting that these cells positively respond to chondrogenic induction. Moreover, considering different growth factor influence on chondrogenic differentiation, it is important to note that there are studies suggesting that TGF- β 3 does not always induce chondrogenesis in such cells as ADSC and BMMSCs, where BMP-2 was shown to act as a major chondrogenic differentiation inducer in ADSC [65, 66], and the combination of TGF- β 1, GDF-5, and BMP-2 stimulated robust chondrogenic response in BMMSCs [67]. These observations may lead to the development of new strategies for novel chondrogenic differentiation protocols for MenSCs, which will include additional factors that these cells may require.…”
Section: Mensc Chondrogenic Differentiation Capability For Tissue mentioning
confidence: 99%
“…Nevertheless, during MenSC differentiation, they detected a significant increase in the expression level of Collagen 9A1 and the transcription factor SOX9, suggesting that these cells positively respond to chondrogenic induction. Moreover, considering different growth factor influence on chondrogenic differentiation, it is important to note that there are studies suggesting that TGF- β 3 does not always induce chondrogenesis in such cells as ADSC and BMMSCs, where BMP-2 was shown to act as a major chondrogenic differentiation inducer in ADSC [65, 66], and the combination of TGF- β 1, GDF-5, and BMP-2 stimulated robust chondrogenic response in BMMSCs [67]. These observations may lead to the development of new strategies for novel chondrogenic differentiation protocols for MenSCs, which will include additional factors that these cells may require.…”
Section: Mensc Chondrogenic Differentiation Capability For Tissue mentioning
confidence: 99%
“…Three days after surgery, the anastomoses with IGF-I coated sutures showed better anastomotic healing (histology appearance) and greater capacity to withstand biomechanical stress (busting pressure) than the control groups [ 23 ]. As an FDA-approved biologic, BMP-2 appears promising in promoting chondrogenesis and cartilage repair at pre-clinical setting [ 27 , 28 , 29 ]. The current study with BMP-2 coating on the resorbable sutures provides evidence to further support the theory that growth factors can be successfully introduced to a local tissue environment by coating suture material.…”
Section: Discussionmentioning
confidence: 99%
“…ADSCs were isolated from the inguinal fat pads of 3-week-old male Lewis rats according to previously reported methods. 24 After being isolated, ADSCs were maintained in complete growth medium (Dulbecco's modified Eagle's medium [DMEM], Invitrogen) containing L-glutamine supplemented with 10% fetal bovine serum (FBS) and 1%…”
Section: Cell Culturementioning
confidence: 99%
“…was negatively correlated in patients with clinical OP. Previous reports have shown that rat primary adipose stem cells have pluripotent differentiation potential and can be induced to differentiate into adipocytes and chondrocytes 24. Bone remodeling is the basis of the process of bone repair or osteogenesis in many skeletal diseases.…”
mentioning
confidence: 99%